PERAN GURU DALAM MENINGKATKAN KREATIVITAS ANAK USIA DINI KELOMPOK B DI TK TAT TWAM ASI,KECAMATAN MAULAFA,KOTA KUPANG - Lamamayan, Odilia; Margiani, Kristin; G. Betty, Credo; Novyani Seran, Theodorina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers in enhancing the creativity of early childhood Group B at Tat Twam Asi Kindergarten, Maulafa District, Kupang City. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects in this study were two class B teachers, and the validity of the data was tested through source technical triangulation. The results of the study show that teachers play a role through four aspects, namely as facilitators, mediators, inspirators, and models. (1) As facilitators, teachers prepare RPPH, learning media, loose part materials, and organize a learning environment that is safe and support children's exploration. (2) As mediators, teachers use stories, songs, imaginative games, and media that are appropriate to the theme and characteristics of children. (3) As inspirators, teachers provide praise, encouragement, and a comfortable learning atmosphere so that children dare to try new things. (4) As models, teachers provide direct examples in learning activities, making it easier for children to understand the steps involved and encouraging them to create. The conclusion of this study is that the teacher's role when effectively implemented through interconnected practices can help enhance the creativity of early childhood learners. However, initial observations also revealed that some children's creativity has not yet developed optimally; therefore, the teacher's role is crucial in creating learning experiences that are meaningful, varied, enjoyable, and child centered. Keywords: teacher role, creativity, early childhood